2022
DOI: 10.3389/fphys.2022.807583
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomic and Lipidomic Analysis in the Placenta of Preeclampsia

Abstract: Preeclampsia is one of the most common severe pregnancy complications in obstetrics, which is considered a placental source disease. However, the mechanisms underlying preeclampsia remain largely unknown. In this study, UPLC-MS/MS-based metabolomic and lipidomic analysis was used to explore the characteristic placental metabolites in preeclampsia. The results revealed that there were significant changes in metabolites between preeclampsia and normotensive placentas. Weighted correlation network analysis (WGCNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…79, 80 Also interesting is a possible association of DPPC and ANXA2 in both lupus and preeclampsia, where increased DPPC can accumulate to form “active hydrophobic spots,” possibly in conjunction with antiphospholipid syndrome and development of autoantibodies against ANXA2. 8185 The connection between ANXA2 and DPPC identified here presents exciting new possibilities for management of disease conditions. As excess DPPC can induce junctional defects in endothelial cells, it will be interesting to determine if that association persists in the conditions listed in Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…79, 80 Also interesting is a possible association of DPPC and ANXA2 in both lupus and preeclampsia, where increased DPPC can accumulate to form “active hydrophobic spots,” possibly in conjunction with antiphospholipid syndrome and development of autoantibodies against ANXA2. 8185 The connection between ANXA2 and DPPC identified here presents exciting new possibilities for management of disease conditions. As excess DPPC can induce junctional defects in endothelial cells, it will be interesting to determine if that association persists in the conditions listed in Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned, placenta is the principal contributor to PE development. Several studies have demonstrated transcriptome and metabolomic profiles in the placentas of PE patients in order to present the molecular network in PE placentas [ 36 , 37 , 38 , 39 ]. The present study has revealed that the molecular pathways such as sphingolipid pathway, OXPHOS, carbon metabolism, glutathione metabolism and mtDNA maintenance were affected in the placentas of a CBX-induced PE-like model.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has revealed that the molecular pathways such as sphingolipid pathway, OXPHOS, carbon metabolism, glutathione metabolism and mtDNA maintenance were affected in the placentas of a CBX-induced PE-like model. Interestingly, these molecular pathways are reported in the placentas of PE patients [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In addition, we found that TNF-α, MMP7, ADAMts5 mRNA levels were increased in the PE-like model, which is consistent with prior studies of human PE placentas where they are implicated to be involved in PE pathogenesis [ 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have uncovered differences in the plasma lipidomic profile of patients with preeclampsia. By conducting ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS)-based metabolomic and lipidomic profiling of placentae, Zhang et al identified significant changes in metabolites between preeclampsia and normotensive patients, which were primarily associated with glycerophospholipids and glutathione metabolism [ 30 ]. Biomembranes are composed of lipids such as glycerophospholipids and sphingolipids that have not only a structural role but could also function as the regulator of signal transduction and immune activation pathways as well as inflammatory response [ 31 ].…”
Section: Lipidomics In Preeclampsia: Current Knowledge and Clinical I...mentioning
confidence: 99%